On semantics and refinement of UML statecharts: a coalgebraic view - Sun Meng (2004)
Statecharts was conceived as a visual formalism for the design of reactive systems. UML statecharts is an object-based variant of classical statecharts, incorporating several concepts different from the classical statecharts. This paper discusses a coalgebraic description of UML statecharts, directly derived from its operational semantics. In particular such an approach induces suitable notions of equivalence and (behavioral) refinement for statecharts. Finally, a few refinement laws are investigated to support verifiable stepwise system development with statecharts.